Therapeutic manipulation of the HIF hydroxylases - Nagel, Simon; Talbot, Nick P.; Mecinović, Jasmin; Smith, Thomas G.; Buchan, Alastair M.; Schofield, Christopher J. (Antioxidants & redox signaling, 2010)
The hypoxia-inducible factor (HIF) family of transcription factors is responsible for coordinating the cellular response to low oxygen levels in animals. By regulating the expression of a large array of target genes during hypoxia, these proteins also direct adaptive changes in the hematopoietic, cardiovascular, and respiratory systems. They also play roles in pathological processes, including tumorogenesis. In recent years, several oxygenases have been identified as key molecular oxygen sensors within the HIF system. The HIF hydroxylases regulate the stability and transcriptional activity of the HIF-α subunit by catalyzing hydroxylation of specific proline and asparaginyl residues, respectively. They require oxygen and 2-oxoglutarate (2OG) as co-substrates, and depend upon non-heme ferrous iron (Fe(II)) as a cofactor. This article summarizes current understanding of the biochemistry of the HIF hydroxylases, identifies targets for their pharmacological manipulation, and discusses their potential in the therapeutic manipulation of the HIF system. Antioxid. Redox Signal. 12, 481-501.